Hubungan Pengetahuan Universal Precaution dengan Kepatuhan Perawat dalam Penggunaan Alat Pelindung Diri (APD) di Ruang Instalasi Bedah Sentral RSD Mangusada - I Made Dwie Pradnya Susila; Ni Putu Nopi Widayanti (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2021)
The incidence of infectious diseases in hospitals is a serious problem because it threatens the health and safety of patients and healthcare workers. Experts agree that compliance with the use of PPE is considered very important to protect the body from infection contamination. There are many factors that can affect nurses compliance in using PPE, one of which is knowledge of universal precaution. This study aims to determine the correlation of universal precaution knowledge with nurses compliance using PPE in the Central Surgical Installation Room Mangusada Hospital. This type of research is quantitative with cross-sectional design, the sample in this study were all nurses in the Central Surgical Installation Room of Mangusada Regional Hospital selected by the total sampling method of 41 respondents. Data were analyzed by nonparametric rho spearman statistical test at the significance level α 0.05, obtained p-value of 0.000<0.05. This shows that there is a very significant correlation between universal precaution knowledge and nurses compliance in the use of PPE in the Central Surgery Installation Room at Mangusada Hospital, so it is expected that health workers, especially nurses, will increase knowledge related to universal precaution and be more obedient in using PPE.